DAMPAK GERAKAN #METOO DI KOREA SELATAN PADA TAHUN 2018-2020 - Sundari Meilanesia; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research explains about the impact of #MeToo Movement in South Korea in 2018-2020. #MeToo Movement was  founded by Tarana Burke, an American woman activist and aims to fight against sexual harassment and sexual violence. A tweet about this #metoo movement was popularized by Alyssa Milano in 2017. This #MeToo momentum then was harnessed by South Korea’s women to accuse the patriarchal which has implications for gender inequality and sexual harassment. Policy changes as a result of the movement also be discussed in this study.This research is a qualitative research that aims to create a systematic and objective picture. The data collection technique used is document analysis. The case of #MeToo in South Korea is analyzed with the theory of social movements against social change. The level of analysis used is the nation state level of analysis.Based on this research, it can be concluded that the #MeToo Movement is still incapable in changing the patriarchal system that is detrimental to women in South Korea. Despite of the policy changes there still has been no significant change as there has been no decrease in the rate of sexual violence. Keywords: #metoo movement, sexual violence, South Korea, feminism